The Effectiveness of Songs as a Phonology-Based English Pronunciation Teaching Tool - Praja Hartama Simanjuntak; Juli Hartati Sihaloho; Natalina Limbong; Bloner Sinurat (Young Journal of Social Sciences and Humanities, 2025)
This study aims to investigate the effectiveness of English songs as a phonology-based tool for teaching pronunciation to EFL learners. The research employed an experimental approach involving intermediate-level students in real classroom settings. Songs were integrated into pronunciation lessons to observe their impact on learners' phonological development, including segmental features (vowels and consonants) and suprasegmental features (intonation, stress, and rhythm). The results showed that students who were taught using English pop songs demonstrated notable improvements in their pronunciation accuracy, listening comprehension, and motivation to learn. The melodic and repetitive nature of songs helped reinforce sound patterns, making pronunciation practice more enjoyable and memorable. These findings support the use of music as an innovative pedagogical strategy in English language classrooms, promoting not only phonological competence but also a more engaging and confidence-building learning environment.